7o Verano de la Investigación Científica - Castillo Serrano, Ma. Soledad; Aragón Jáuregui, Carmen; López de Alba, Pedro Luis (Acta Universitaria, 2001)
The sixth edition of the institutional program “Verano de la Investigación científica de la Universidad de Guanajuato” (Scientific Research Summer of the University of Guanajuato) was held from July 3 to August 4, 2000 in which the research results of 32 undergraduate students were presented and the abstracts of these results have been compiled in the present document. Six of the 32 undergraduate students came from the State of Tabasco and were financed by the Consejo de Ciencia y Tecnología (Science and Technology Council of the State of Tabasco) of that state and 26 were from the University of Guanajuato and were supported by the Institution. These students belong to the following fields of learning: Social Sciences and Humanities, 6; Health, 4; Engineering, 5; Natural Sciences, 16; and Economics & Administration, 1.